Preparation of SS316L MIM feedstock with biopolymer as a binder - Abdullah, Abu; Hassan, Norita; Hassan, Noor Azlina; Sulong, Abu Bakar; Mas'Ood, Najlaa Nazihah (Institute of Physics Publishing, 2018)
This paper focus on feedstock preparation for SS316L metal injection molding (MIM) part. The primary step of feedstock preparation, critical powder loading determined by two method; maximum filled volume calculation model and torque analysis. The critical powder loading determined by calculation was 70 vol% to 77 vol% while for experimental approaches shows the value of 75 vol%. The feedstock was prepared by mixing SS316L powder and polymer binder with ratio 70:30 at 175 °C with speed of 50 rpm. The feedstock was analyzed by thermogravimetric analysis (TGA) and Scanning electron microscope (SEM). The composition for the feedstock after preparation step was confirmed by TGA. It was found that the prepared feedstock component was compatible to each other and composition is maintain along the mixing step.